THE PREFERENCES AND DISTRIBUTION OF SUGARCANE SCALE INSECT Aulacaspis tegalensis (HEMIPTERA: DIASPIDIDAE) ON DIFFERENT CLONES OF SUGARCANE - Pramono, Sudi; Wagiman, Franciscus Xaverius; Trisyono, Yohanes Andi; ., Witjaksono (Universitas Lampung, 2020)
This research was conducted in the field of Gunung Madu Plantations Co., Gunung Batin, Lampung Tengah, in the period of April 2015–May 2016. The experiment was arranged in a randomized completely block design with six sugarcane clones as treatments (GMP 1, GMP 2, RGM 99.370, RGM 97.8837, GMP 3, and GMP 4) and four blocks, every block was separated by the street. The abundance of sugarcane scale insects was observed in 15-day intervals from the plant ages of 4 to 12 months. The results showed that sugarcane clone affected the abundance of sugarcane scale insects. After a lag phase of six months (fifth observation), the sugarcane scale insects started being found on all six sugarcane clones in the field. The abundance of the scale insects then increased and peaked at 10.5 months. The sugarcane scale insects attacked all six clones of sugarcane. Clone GMP 1 was the most preferred with an average scale abundance at 814.4 individuals/stem while the least preferred clone was GMP 4 with average of 179 individuals/stem.